Elaboration of a POSAI-POSAI combinated electrode for acid-base microtiter - Pérez-Saavedra, José de Jesús (2013)
We present the design, construction and testing of a combined electrode oxide films over stainless steel (POSAI) as indicator electrode and reference electrode. This electrode is used to make micropotentiometry acid/base (acetic acid and phosphoric acid with sodium hydroxide, sodium acetate with nitric acid). A “t Student test” was applied, showing that there is no significant difference with micropotentiometry carried out with a conventional glass electrode.